Blood Rheology: Key Parameters, Impact on Blood Flow, Role in Sickle Cell Disease and Effects of Exercise - Nader, Elie; Skinner, Sarah; Romana, Marc; Fort, Romain; Lemonne, Nathalie; Guillot, Nicolas; Gauthier, Alexandra; Antoine-Jonville, Sophie; Renoux, Céline; Hardy-Dessources, Marie-Dominique; Stauffer, Emeric; Joly, Philippe; et al. (Frontiers in Physiology, 2019)
Blood viscosity is an important determinant of local flow characteristics, which exhibits shear thinning behavior: it decreases exponentially with increasing shear rates. Both hematocrit and plasma viscosity influence blood viscosity. The shear thinning property of blood is mainly attributed to red blood cell (RBC) rheological properties. RBC aggregation occurs at low shear rates, and increases blood viscosity and depends on both cellular (RBC aggregability) and plasma factors. Blood flow in the microcirculation is highly dependent on the ability of RBC to deform, but RBC deformability also affects blood flow in the macrocirculation since a loss of deformability causes a rise in blood viscosity. Indeed, any changes in one or several of these parameters may affect blood viscosity differently. Poiseuille’s Law predicts that any increase in blood viscosity should cause a rise in vascular resistance. However, blood viscosity, through its effects on wall shear stress, is a key modulator of nitric oxide (NO) production by the endothelial NO-synthase. Indeed, any increase in blood viscosity should promote vasodilation. This is the case in healthy individuals when vascular function is intact and able to adapt to blood rheological strains. However, in sickle cell disease (SCD) vascular function is impaired. In this context, any increase in blood viscosity can promote vaso-occlusive like events. We previously showed that sickle cell patients with high blood viscosity usually have more frequent vaso-occlusive crises than those with low blood viscosity. However, while the deformability of RBC decreases during acute vaso-occlusive events in SCD, patients with the highest RBC deformability at steady-state have a higher risk of developing frequent painful vaso-occlusive crises. This paradox seems to be due to the fact that in SCD RBC with the highest deformability are also the most adherent, which would trigger vaso-occlusion. While acute, intense exercise may increase blood viscosity in healthy individuals, recent works conducted in sickle cell patients have shown that light cycling exercise did not cause dramatic changes in blood rheology. Moreover, regular physical exercise has been shown to decrease blood viscosity in sickle cell mice, which could be beneficial for adequate blood flow and tissue perfusion.